2008
DOI: 10.1606/1044-3894.3709
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers of Older Clients with Severe Mental Illness: Perceptions of Burdens and Rewards

Abstract: Approximately 1 million older persons have a severe mental illness (SMI) and this number is expected to double in the coming decades. While research studies have examined the experiences of family members of younger persons with SMI, very little is known about caregivers of older SMI clients. This study examined the characteristics, burdens, and rewards of 60 caregivers of older SMI clients using a modified version of family caregiver scales of Tessler, Fisher, & Gamache (1992). Hierarchical linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…Auslander and Jeste (2002) found that older clients with psychiatric disorders encounter on-going service needs related to communication and interpersonal relationships. Other researchers indicate that intimate relations and social contact needs are among those most often cited by older SMI clients and those that most frequently remain unmet (Cummings & MacNeil, 2008;McNulty, Duncan, Semple, Jackson, & Pelosi, 2003). Other social functioning needs of older adults with SMI include assistance with money, learning about potential benefits, handling domestic skills, homemaking chores, and transportation (Bengtsson-Tops & Hannson, 1999;Cummings & Cassie, in press;LeiBe & Kallert, 2003;McNulty et al, 2003).…”
Section: Services Needs Of Older Smi Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Auslander and Jeste (2002) found that older clients with psychiatric disorders encounter on-going service needs related to communication and interpersonal relationships. Other researchers indicate that intimate relations and social contact needs are among those most often cited by older SMI clients and those that most frequently remain unmet (Cummings & MacNeil, 2008;McNulty, Duncan, Semple, Jackson, & Pelosi, 2003). Other social functioning needs of older adults with SMI include assistance with money, learning about potential benefits, handling domestic skills, homemaking chores, and transportation (Bengtsson-Tops & Hannson, 1999;Cummings & Cassie, in press;LeiBe & Kallert, 2003;McNulty et al, 2003).…”
Section: Services Needs Of Older Smi Adultsmentioning
confidence: 99%
“…While some research on the formal services available to assist the older adults with SMI does exist, much less is known about the amount and types of informal support available to assist older adults with severe psychiatric diagnoses. Cummings and MacNeil (2008) conducted research with 60 caregivers of older adults with SMI. The majority of these caregivers were either adult children (40%) or siblings (18%).…”
Section: Sources Of Assistance For the Older Smi Populationmentioning
confidence: 99%
“…Coping with the strain of shifting roles, subjective and objective challenges of caregiving, and stigma can stress family members (Schulze and Rössler 2005). On the other hand, it can create positive and rewarding experiences including a sense of fulfillment for the caregiver, engagement with the ill family member, and closer family relationships (Chen and Greenberg 2004;Cummings and MacNeil 2008). On the other hand, it can create positive and rewarding experiences including a sense of fulfillment for the caregiver, engagement with the ill family member, and closer family relationships (Chen and Greenberg 2004;Cummings and MacNeil 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Family members of persons with serious mental illnesses, including schizophrenia, major depressive disorder, bipolar disorder, panic disorder, and others, have received limited attention [13, 14]. Individuals who have a family member diagnosed with a serious mental illness are at risk for poor health and low quality of life because of the stress and stigma by association that they experience [15, 16].…”
Section: Introductionmentioning
confidence: 99%